On the adaptive flexibility of evaluative priming - Fiedler, Klaus; Blümke, Matthias; Unkelbach, Christian (Memory & cognition, 2011)
If priming effects serve an adaptive function, they have to be both robust and flexible. In four experiments, we demonstrated regular evaluative-priming effects for relatively long stimulus-onset asynchronies, which can, however, be eliminated or reversed strategically. When participants responded to both primes and targets, rather than only to targets, the standard congruity effect disappeared. In Experiments 1a-1c, this result was regularly obtained, independently of the prime response (valence or gender classification) and the response mode (pronunciation or keystroke). In Experiment 2, we showed that once the default congruity effect was eliminated, strategic-priming effects reflected the statistical contingency between prime valence and target valence. Positive contingencies produced congruity, whereas negative contingencies produced equally strong incongruity effects. Altogether, these findings are consistent with an adaptive-cognitive perspective, which highlights the role of flexible strategic processes in working memory as opposed to fixed structures in semantic long-term memory or in the sensorimotor system.
Published: 16 December 2010
Gesehen am 09.05.2022